Perioperative Outcomes of the Patients with Obstructive Sleep Apnoea (The Planet, 2023)
Background: Obstructive sleep apnea (OSA) is a chronicmedical disorder that causes the upper airway to becomepartially or completely blocked while the patient is sleeping.This syndrome is associated with high rates of death andincreases the risks faced by patients during surgery.Objective: The study aims to observe the perioperativeoutcomes of the patients with obstructive sleep apnoea.Method: The present cross-sectional investigation wascarried out over a four-year period, spanning fromFebruary 2019 to February 2023, at the Department ofAnaesthesiology located at the Holy Family Red CrescentMedical College & Hospital in Dhaka, Bangladesh. Thesample size for this study was intentionally chosen to consistof 200 cases. Results: In our study, maximum patients (43%)were between 30 to 40 years age group and minimumpatients (4.5%) were more than 60 years old. Maximum patients (54%) were female patientsand minimum patients (46%) were male patients. Maximum patients (35.5%) had sleepinessand minimum patients (8.5%) had personality change. Maximum patients (49%) usedsevoflurane and minimum patients (6%) used isoflurane in our study. Maximum (46%)anesthetists had more than 20 years’ experience and minimum (5%) anesthetists had 6 to 10years’ experience. Conclusion: There is a need for updating the medical knowledge pertainingto OSA. It is recommended that a pragmatic manual be developed to assist medicalpractitioners in identifying individuals with obstructive sleep apnea (OSA) and to establish auniform approach to preoperative and perioperative care.
Keywords: Obstructive sleep apnea; Perioperative management; Anesthesia